2019
DOI: 10.1111/cch.12649
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory analysis and normative tables for the Brazilian Ages and Stages Questionnaires: Social–Emotional

Abstract: BackgroundIn Brazil, large‐scale governmental programmes have been implemented to evaluate the development of all children who are enrolled in public daycare centres and preschools using the Brazilian Ages and Stages Questionnaires: Social–Emotional (ASQ:SE) as a screening tool. However, in the Brazilian context, there is a lack of studies that have investigated the clinical utility of the ASQ:SE, and only a few studies have partially investigated the psychometric properties of the Brazilian version of this sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…The Ages and Stages Questionnaire: social-emotional (ASQ:SE) by Squires et al (1997) [35] consists of questionnaires with 16, 23 and 27 items measuring the infant's socio-emotional behaviour by self-regulation, compliance, adaptive functioning, autonomy, affect, social communication and parent-child interaction. The ASQ:SE has been validated in several countries and shown a moderate to good sensitivity (71-85%) and an excellent specificity of (90-98%) [36][37][38]. Each item is rated on a three-point scale, and the ASQ:SE score is calculated ranging from 0 to 15; low scores are favourable.…”
Section: Discussionmentioning
confidence: 99%
“…The Ages and Stages Questionnaire: social-emotional (ASQ:SE) by Squires et al (1997) [35] consists of questionnaires with 16, 23 and 27 items measuring the infant's socio-emotional behaviour by self-regulation, compliance, adaptive functioning, autonomy, affect, social communication and parent-child interaction. The ASQ:SE has been validated in several countries and shown a moderate to good sensitivity (71-85%) and an excellent specificity of (90-98%) [36][37][38]. Each item is rated on a three-point scale, and the ASQ:SE score is calculated ranging from 0 to 15; low scores are favourable.…”
Section: Discussionmentioning
confidence: 99%
“…First, the solution obtained from PCA and FA methods completely agreed in terms of placing the item in its factor with the greater loading, with results reproducing some previously published evidence. 15,38 From the statistical angle, both methods analyze the internal structure of a psychological test via multivariate analysis and some literature further considers that FA is a generalization of PCA. 39 The overlapping findings that were produced by these two approaches have mathematical foundations in the way the decomposition of variance is performed.…”
Section: Discussionmentioning
confidence: 99%
“…19 Previous cross-country studies that have used EFA and confirmatory factor analysis, as well as item response theory have concluded that the variability of ASQ:SE observed variables can be adequately explained in two dimensions namely a social and an emotional one. 15,20,21 The ASQ: SE has been widely recognized as a useful screening tool for practitioners, clinicians, and families to identify children who may be facing a challenging environment or may be at risk of developmental delays. 19 In this study, the ASQ:SE 60-month-old children were selected for the sample, as social and emotional skills are most easily discriminable in the age of 5, as pointed out by the specific literature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Para verificação da adequação do modelo aos dados, utilizou-se como Goodness of Fit os ajustes obtidos pela estatística M2 (p ≥ 0,05) e pela Raiz Quadrada Média dos Quadrados dos Erros de Aproximação (RMSEA) ou a Raiz Padronizada da Média Quadrática Residual (SRMSR) (valor ≤ 0,08). Esses indicadores têm se mostrado importantes na verificação dos modelos da Teoria de Resposta ao Item (TRI) 29 . Complementarmente, os resultados ≥ 0,9 do Índice de Ajustamento Comparativo (CFI) e do Índice de Tucker-Lewis (TLI) também foram utilizados como critérios de evidência 28 .…”
Section: Análise Estatística De Dadosunclassified